A Study on Factors Influencing Job Satisfaction of Faculty Members of Self Finance College Lecturer: A correlation analysis of job satisfaction factors among faculty members in self finance colleges (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In the dynamic global economy our students have a greater employment opportunity. With nearly 140 million people in the college-going age group, one in every four graduates in the world will be a product of the Indian education system. Higher education in India has recorded impressive growth since Independence. Hence India has to compete with global economy where we need qualified faculties. Here the faculties have played a major role in our educational system. Job satisfaction of the faculty members plays a vital role among students’ education. When teachers are satisfied with their job then only they can perform their responsibilities with more concentration and devotion. Job satisfaction among college teachers is good not only for themselves but society as a whole. Job satisfaction differs from person to person. The factors determines job satisfaction vary according to gender, age, experience, and position. With this background data have been collected from the faculty members those who are working in the colleges in around. This study attempts to evaluate job satisfaction of teachers in different colleges in. It focuses on the factors deciding the job satisfaction of the teachers and the impact on their performance. Correlation analysis used to test the hypothesis.